The logic of racial practice : explorations in the habituation of racism - Bahler, Brock, 1981-; Yancy, George (Philosophy of race., 2021)
This book explores how white supremacy produces a racialized orientation in our lives, arguing that racism is habituated, enacting within us racialized and racist dispositions and bodily comportments that inform how we interact with others.